The association between falls and depressive symptoms among older adults: evidence from the China Health and Retirement Longitudinal Study - Feng, Zhiqiang; Chen, Qi; Li, Yanjing; Xue, Zhen; Hao, Xiaoning (Frontiers in Public Health, 2023)
Background: Falls place a heavy burden on older adults and families, and there was little research on the relationship between falls and depressive symptoms among older adults in China. This study is designed to examine the association between falls and depressive symptoms in Chinese older adults. Methods: This study was based on 9539 data sets from the China Health and Retirement Longitudinal Study (CHARLS) in 2018. The 10-item Center for Epidemiologic Studies-Depression Scale (CESD-10) was used to access depressive symptoms in older adults. A logistic regression model was used to calculate multivariate odds ratios (ORs) and 95% confidence intervals (CIs) for falls and depressive symptoms, adjusted for possible confounders. The Classification and regression tree (CART) demonstrates the prediction of the target variable values based on other variables. Results: In this study, 9,539 older people were selected: 60-69 years old accounted for 63.0%, 70-79 years old accounted for 29.7%, and 80 years old and above accounted for 7.3%. Male accounted for 49.7% and female for 50.3%. The rate of falls among older adults was 21.4%, and the rate of depressive symptoms was 33.9%. Adjusted ORs (OR =1.37, 95% CI: 1.23, 1.53) showed a significant association between falls and depressive symptoms among older adults. Subgroup analysis revealed that this association was statistically significant across male (OR =1.29, 95% CI: 1.23, 1.53) and female (OR =1.42, 95% CI: 1.23, 1.64), 60-69 aged (OR =1.38, 95% CI: 1.19, 1.60) and 70-79 aged (OR =1.42, 95% CI: 1.16, 1.74), rural (OR =1.42, 95% CI: 1.25, 1.61), less than 15000 CNY (OR =1.35, 95% CI: 1.19, 1.54) and more than 25000 CNY (OR =1.42, 95% CI: 1.09, 1.85). Additionally, The CART model showed that the probability (73.0%) of falls was highest among older adults with depressive symptoms who self-rated poor health and female gender. Conclusions: This cross-sectional study demonstrated a significant association between falls and depressive symptoms in Chinese older adults. The findings provide some evidence and support for risk monitoring, screening for depressive symptoms, and early prevention in the high-risk elderly population.